Caracterização da região 5'-terminal de um isolado brasileiro do Southern bean mosaic virus - Espinha, Luciana M. [UNESP]; Gaspar, José O. [UNESP]; Ward, Richard J.; Ruller, Roberto; Camargo, Luis E. A. (Sociedade Brasileira de Fitopatologia, 2004)
We report the characterization of the 5'-terminal region of an isolate of Southern bean mosaic virus found in the São Paulo State, Brazil (SBMV-SP). The RNA was extracted from purified virus particles and subjected to RT-PCR using oligonucleotides designed to amplify about 590 nt of the 5'-terminal region of the viral RNA. A fragment with the expected size was obtained, which, after cloning and sequencing, showed the existence of a 5' non-coding region with 92 nt and the first ORF, starting at the first AUG (position 93) and ending at a UGA stop codon at position 534. A small site, partially complementary to the 3'-terminus of 18S ribossomal RNA was detected at the non-coding region. The ORF1 may encode a protein containing 147 amino acids with a deduced molecular weight of 17080 Da. The 3'-terminus of ORF1 overlaps the 5'-terminus of ORF2 in 34 nt. Our results indicate that the 5'-terminal region of SBMV-SP is similar to that of the Arkansas isolated (SBMV-ARK) described in the North America.

O presente trabalho caracteriza a região 5'-terminal de um isolado do Southern bean mosaic virus encontrado no Estado de São Paulo (SBMV-SP). O RNA foi extraído de partículas virais purificadas e submetido a RT-PCR usando oligonucleotídeos desenhados para amplificar cerca de 590 nt da região 5'-terminal do RNA viral. Foi obtido um fragmento de tamanho esperado que, após clonagem e seqüenciamento, mostrou a existência de uma região não codificadora com 92 nt e a primeira ORF, começando no primeiro AUG (posição 93) e terminando no códon UGA na posição 534. Na região não codificadora foi detectado um segmento parcialmente complementar ao RNA ribossomal 18S. A ORF1 codifica uma proteína de 147 aminoácidos com massa molecular estimada de 17080 Da. A extremidade 3' da ORF1 sobrepõe a extremidade 5' da ORF2 em 34 nucleotídeos. Os resultados obtidos indicam que a região 5'-terminal do RNA do SBMV-SP é similar ao isolado Arkansas (SBMV-ARK) descrito na América do Norte.
Characterization of the 5'-terminal region of a Brazilian isolate of Southern bean mosaic virus
Keywords: feijoeiro comum; Sobemovirus; SBMV; seqüenciamento